2018
DOI: 10.1108/rpj-02-2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behavior of additively manufactured Ultem 1010: experiment and simulation

Abstract: Purpose The purpose of this paper is to study the flexural behavior of additively manufacture Ultem 1010 parts. Fused deposition modeling (FDM) process has become one of most widely used additive manufacturing methods. The process provides the capability of fabricating complicated shapes through the extrusion of plastics onto a print surface in a layer-by-layer structure to build three-dimensional parts. The flexural behavior of FDM parts are critical for the evaluation and optimization of both material and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Gomez-Gras et al (2018) observed that fill density was the most prominent process parameter followed by nozzle diameter and layer thickness on fatigue life. Taylor et al (2018) studied the consequence of build orientation and raster angle on flexural strength of parts made of ULTEM 1010 (unfilled polyetherimide – a semi-transparent high strength material) material experimentally and numerically. Gebisa and Lemu (2018) found that the raster width and raster angle had the maximum effect on the flexural properties of ULTEM 9085 components.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…Gomez-Gras et al (2018) observed that fill density was the most prominent process parameter followed by nozzle diameter and layer thickness on fatigue life. Taylor et al (2018) studied the consequence of build orientation and raster angle on flexural strength of parts made of ULTEM 1010 (unfilled polyetherimide – a semi-transparent high strength material) material experimentally and numerically. Gebisa and Lemu (2018) found that the raster width and raster angle had the maximum effect on the flexural properties of ULTEM 9085 components.…”
Section: Fused Deposition Modelling Part Quality and Performance Improvementmentioning
confidence: 99%
“…The use of these strategies has reported improvements in the mechanical properties of the composites. For instance, Taylor et al used atmospheric plasma to increase the adhesion of BF to a PP matrix processed by FFF and increasing its flexural modulus by 12% [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Motaparti and her colleagues [23] studied the relationship between build direction, raster angle of the filling, and air gap with compression properties at different temperatures on ULTEM™ 9085 parts produced by filament AM. Taylor and his colleagues, in 2018, carried on Motaparti's research by producing ULTEM™ 1010 specimens with varying raster angles and building direction to evaluate how these parameters would affect flexural properties [24]. They developed a simulation of the flexural experiment and validated it with the performed tests.…”
Section: Effect Of Kinematic Process Parametersmentioning
confidence: 99%